“I was afraid they will be judging me and even deny me the service”: Experiences of denial and dissuasion during abortion care in Ethiopia - Bercu, Chiara; Jacobson, Laura E.; Gebrehanna, Ewenat; Ramirez, Ana Maria; Katz, Anna J.; Filippa, Sofía; Baum, Sarah E. (Frontiers in Global Women's Health, 2022)
Introduction: Disrespect and abuse is a component of poor quality of abortion care. This analysis aimed to understand negative experiences of care from perspectives of abortion clients in public and private facilities in Ethiopia. Study Design: We conducted 23 in-depth interviews with people who obtained abortion care in Addis Ababa, Ethiopia as well as Aksum and Mekele in Tigray State, Ethiopia. The interviews were coded using a priori and emergent codes and we conducted thematic analysis to understand negative interactions with providers from participant’s perspectives. Results: Participants experienced denial of abortion services along their pathway to care and attempts by providers to dissuade them prior to providing an abortion. Underlying both the denial and the dissuasion were reports of disrespect and condemnation from providers. Participants described how providers doubted or forced them to justify their reasons for having an abortion, stigmatized them for seeking multiple abortions or later abortions, and ascribed misinformation about abortion safety. Despite reports of denial, dissuasion, and disrespect, abortion clients generally felt that providers had their best interest at heart and were grateful for having access to an abortion. Conclusions: Participants in Ethiopia experienced providers as gatekeepers to legal abortion care, and disrespect and judgment at facilities where they sought care. Increasing awareness and normalizing abortion may reduce barriers to accessing legal services. In order to improve quality of care, interventions may also be needed for providers to address values clarification specifically around abortion decision-making.